2016
DOI: 10.18869/acadpub.jrh.6.5.479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of critical thinking training on the psychiatric nurses’ job satisfaction

Abstract: Nurses are of the most important staff in health systems. Nurses' job satisfaction is an important issue in the nursing management. The aim of this study is to determine the effect of critical thinking training on the nurses of psychiatric wards' job satisfaction. In this study, 54 participants were divided into two groups by random allocation. Brayfield & rothe job satisfaction questionnaire was used as the scale for data collection in three stages; before intervention, 1 month, and 2 month after the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
6
2
1
Order By: Relevance
“…Furthermore, relationships with co-workers have been based not only on a single factor but they involved multiple factors (Cabelkova, Abrham, & Strielkowski, 2015;Clossey, Solomon, Hu, Gillen, & Zinn, 2018;Dalkilic, Cimen, & Ramazanoglu, 2015). On the other side, the current study had differed from the study findings already conducted by some researchers in both the developing and developed worlds (Dordunu, Owusu, & Simpson, 2020;Heydari, Meshkinyazd, & Soudmand, 2017;Qadri, Hassan, & Sheikh, 2017;Zakariaa & Abdullahc, 2018).…”
Section: Hypothesis 3: Relationship With Co-workers Pay and Promotion...contrasting
confidence: 61%
“…Furthermore, relationships with co-workers have been based not only on a single factor but they involved multiple factors (Cabelkova, Abrham, & Strielkowski, 2015;Clossey, Solomon, Hu, Gillen, & Zinn, 2018;Dalkilic, Cimen, & Ramazanoglu, 2015). On the other side, the current study had differed from the study findings already conducted by some researchers in both the developing and developed worlds (Dordunu, Owusu, & Simpson, 2020;Heydari, Meshkinyazd, & Soudmand, 2017;Qadri, Hassan, & Sheikh, 2017;Zakariaa & Abdullahc, 2018).…”
Section: Hypothesis 3: Relationship With Co-workers Pay and Promotion...contrasting
confidence: 61%
“…The total score of job satisfaction ranges from 19 to 95. Heydari et al 43 confirmed the content validity of this scale with expert panel. The reliability of this index was confirmed with a Cronbach’s alpha of 0.93.…”
Section: Methodsmentioning
confidence: 77%
“…The competency possessed by nurses contributes to their satisfaction in providing spiritual services to patients. This results in an increase in nurses' understanding after receiving spiritual education, which undoubtedly has a psychological effect on nurses (Heydari et al, 2017). Moreover, spiritual education through training also has a positive behavioral impact on individuals, forming the basis for the cultivation of high moral values, particularly in caring for others, including patients (Jalili et al, 2020).…”
Section: Discussionmentioning
confidence: 99%